Panic disorder aging characteristics: The role of telomerase reverse transcriptase gene and brain function - Ding, Huachen; Zhong, Yuan; Liu, Na; Wu, Huiqin; Xu, Huazhen; Wu, Yun; Liu, Gang; Yuan, Shiting; Zhou, Qigang; Wang, Chun (Frontiers in Aging Neuroscience, 2022)
Panic disorder (PD) causes serious functional damage and disability and accelerates the process of individual aging. The pathological basis of PD is the same as that of age-related diseases, which is proposed as a new viewpoint in recent years. Memory decline and social functional impairment are common manifestations of accelerated aging in PD. The function of telomerase reverse transcriptase (TERT) and telomere length (TL) is abnormal in patients with aging and PD. However, the molecular mechanism behind remains unclear. The purpose of this study was to explore the relationship between TERT gene expression (including DNA methylation) and the changes in PD aging characteristics (memory and social function). By TERT gene knockout mice, we found that loss of TERT attenuated the acquisition of recent fear memory during contextual fear conditioning. This study reported that a significantly lower methylation level of human TERT (hTERT) gene was detected in PD patients compared with healthy control and particularly decreased CpG methylation in the promoter region of hTERT was associated with the clinical characteristics in PD. Regional homogeneity (ReHo) analysis showed that the methylation of hTERT (cg1295648) influenced social function of PD patients through moderating the function of the left postcentral gyrus (PCG). This indicates that the hTERT gene may play an important role in the pathological basis of PD aging and may become a biological marker for evaluating PD aging. These findings provide multidimensional evidence for the underlying genetic and pathological mechanisms of PD.